Effect of arbuscular mycorrhiza in the growth, photosynthesis and foliar anatomy on young plants of Agave tequilana - Pimienta-Barrios, Eulogio; Zañudo-Hernández, Julia; López-Alcocer, Eduardo (Instituto de Ecología, A.C., 2009)
The effect of vesicular arbuscular micorrhizal symbiosis (VAM) in growth, seasonal photosynthesis, and foliar anatomy was evaluated on young plants of Agave tequilana. These were established in pots and inoculated with one of two strains of VAM fungi: Glomus fasciculatum (Gf) or Glomus intraradices (Gi), and compared with control plants without inoculation. To evaluate these treatments a completely randomized experimental design was used with six replications and 18 experimental units. The physiological and morphological variables evaluated were: photosynthetic rate, number of young leaves, length and thickness of mature leaves, and percentage of root colonization by VAM fungi. The inoculation increased photosynthetic rate, which was highest in plants inoculated with the Gi strain than both those inoculated with the Gf and the control plants, and it was related with an increase in mesophyll thickness that was most noticeable in the chlorenchyma tissue. However, the variables related to growth, length and width of leaves were unaffected.